Analisis Sistem Penjaminan Mutu Internal (SPMI) SMA Negeri di Kota Mataram - Gunawan, Gunawan; Ramdani, Agus; Fahruddin, Fahruddin (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
Education quality standards are important things that must be possessed by educational institutions including at the level of the education unit. The quality assurance that has been running so far is still limited to external quality assurance, while the internal quality assurance of the Education unit has not been widely implemented by every Education unit. This study aims to determine how the implementation and evaluation of the education quality assurance system in SMAN 6 Mataram City. The method used is descriptive qualitative. Data collection was carried out through interviews, observation and documentation. Data analysis shows that SMA Negeri 6 Mataram is in implementing quality compliance, from the results of interviews with researchers with the principal, deputy principal and head of the TPMPS Team, it is found that all school components are actively involved in school activities, both in analyzing activities and program design and having commitment which is high for the fulfillment of the quality compliance component, this can be seen from the involvement in participating in the activities and programs that have been planned by the school. Based on these findings, it is suggested that 1) SMAN Kota Mataram need to implement quality assurance under certain operational units, 2) empower school administrators by implementing school-based management, 3) there is a need for teachers and administrative staff to be educated about the importance of quality culture.